The Relationship of Peer Group Roles with Verbal Bullying at St. Peter High School Medan - Murniati Br Sitepu; Lilis Novitarum; Floresta Br Sitepu; Putri Indah Manalu (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Peer Group is a group of peers who interact with each other and influence the formation of attitudes, values and behaviors both in social activities, education, and shared hobbies, this can have positive or negative impacts on adolescents. The positive impacts of peer groups such as increasing learning motivation, discipline in rules, positive emotional encouragement towards social to make a teenager more independent, but this can also have negative impacts including uncontrolled free association, truancy behavior from school, cheating on exams, smoking, premarital free association, hedonism, consumptive and bullying behavior which is psychological violence behavior both verbally and non-verbally. This study aims to determine the relationship between peer groups and verbal bullying of adolescents. The results of the study obtain that the majority of peer groups were in the strong category as many as 75 respondents (98.7%) and Verbal bullying was found, verbal bullying do not occur as many as 68 respondents (89.5%). Data analysis using the Fisher exact test, the results of the statistical test obtains a p-value = 1.000 which means that there is no relationship between the role of peer groups and verbal bullying. It is hoped that SMA Santo Yosef Medan students will be able to increase positive peer groups.